Ветвистоусые ракообразные (Crustacea, Cladocera) водоемов Полесского заповедника - Радзимовский, В.Д. (Вестник зоологии, 1980)
32 taxons of Cladocera are found in the Polessie reservation (Zhitomir Region, Ukr. SSR), their complexes are distinguished. The species whose basic area of distribution is within the northern and southern regions of Palearctic and those rare for the Ukrainian Polessie are marked. It is shown that the Cladocera composition specific for sphagnum bogs is preserved in the reservation.